Unmasking of the President Joko Widodo Ideolgy Stances Realized in His Political Speech towards the People of Indonesia - Megah, Suswanto Ismadi; Noor, Siti Noor Mohd.; Latif, Azmi Abdul (Universitas Negeri Semarang, 2021)
This paper aims to unmask President Joko Widodo (Jokowi, henceforth) ideology through his presidential speech. Using a combination of CDA and SFL as an analytical tool of appraisal system, particularly the subsystem of attitude to dismantle ideological stances behind the speech text toward the People of Indonesia. The data was obtained from the first state speech of Jokowi in 2015. Further, selecting the first state speech was the parameter of his leadership in ruling the nation. The results show that Jokowi employed all subtypes of attitude to the people of Indonesia. The subtype of Judgment mostly with positively-invoked capacity employed by Jokowi indicates that He has an ideological inclination to judge the people's character as the capable people who can overcome the worst condition. Therefore, Jokowi implicitly shows his ideological inclination toward the people that he inclination to prioritize the Indonesian people.